2017
DOI: 10.1016/j.chemosphere.2017.02.154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pentachlorophenol on the quail ( Coturnix japonica ) liver detoxification pathway

Abstract: Pentachlorophenol (PCP), an extensively used pesticide and biocide, is of critical environmental concern due to its toxicity and recalcitrance to degradation. In this study, the effect of PCP on induction of transcription factors, cytochrome P450 (CYP450) genes, and the antioxidative enzyme system were investigated in the quail liver. A total of 60 (4- to 6-week-old) male quails (Coturnix japonica) were administered 0, 0.05, 0.5, and 5 mg/kg/d PCP orally for 42 d. Following exposure, both absolute and relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Huang et al (2015) showed that heat exposure of broiler increased lipid peroxidation and 8-OHdG concentration in plasma. In another study, exposure to pentachlorophenol, which is an extensively used pesticide with toxicity, induced an increase in liver 8-OHdG concentration in quail (Jiang et al 2017). In the present study, plasma 8-OHdG concentrations did not change by supplementations of catechin, copper or their combination in laying quail diet.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Huang et al (2015) showed that heat exposure of broiler increased lipid peroxidation and 8-OHdG concentration in plasma. In another study, exposure to pentachlorophenol, which is an extensively used pesticide with toxicity, induced an increase in liver 8-OHdG concentration in quail (Jiang et al 2017). In the present study, plasma 8-OHdG concentrations did not change by supplementations of catechin, copper or their combination in laying quail diet.…”
Section: Discussionsupporting
confidence: 46%
“…The 8-OHdG, which is a critical biomarker of oxidative damage, permanently occurs to lipids of cellular membranes, proteins and DNA and carcinogenesis (Huang et al 2015;Jiang et al 2017). Huang et al (2015) showed that heat exposure of broiler increased lipid peroxidation and 8-OHdG concentration in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduced dopamine levels in the brain indicate that ATR affects the metabolism of dopamine, which results in neurodegenerative disorders . The cytochrome P450 system (CYP450s) belongs to a multigene family of heme proteins that, in addition to their role in the metabolism of xenobiotics (such as ATR) in hepatocytes, are also expressed in neurocytes. , Exogenous substances interact with the CYPs, generating oxidation products that cause biological macromolecules damage and then tissue injury. It is generally known that the metabolism of xenobiotic via alterations in the CYP450s provides useful biomarkers to the field of ecotoxicology assays . Several reports support an emergent role of CYP450s in the pathogenesis of neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The most important target tissue is liver. Depending on the exposed dose, in addition to the some changes in the biochemical parameters, hepatic P450 enzyme activities, liver weight and in the liver microscopy are also observed (24,25,29,38,49). PCP has also toxic effects on kidneys.…”
Section: Introductionmentioning
confidence: 99%